Pengembangan Media Pembelajaran Berbasis Video menggunakan Adobe Flash CS6 Peran dan Dampak Komputer TIK Kelas VII SMP Negeri 8 Kabupaten Sorong - Maria Selviana Mia Pera; Sahiruddin Sahiruddin; Indri Anugrah Ramadhani (Uranus: Jurnal Ilmiah Teknik Elektro, Sains dan Informatika, 2024)
The low quality of learning and learning assessment, has not been integrated into a system properly. So that the ideal learning process cannot occur. The purpose of this study is to determine the ICT learning media Adobe Flash Cs6 for class VII students of Smp Negeri 8 Sorong Regency Based on Video that is Valid and Effective to use. This study uses the development method (Research and Development). Data was collected by observation, interviews, literature studies and questionnaires. The subjects of this study were 21 students of Smp Negeri 8 Sorong Regency class VII. Based on the results of the research on the development of video-based learning media using Adobe Flash Cs6, the validation results were obtained from two validators, including material experts, namely an average percentage of 75% and media experts, namely an average percentage of 94% which is included in the "Very Valid" criteria. the level of effectiveness of learning media was obtained from the respondent questionnaire, the results obtained were an average percentage of 86% which was included in the "Very Effective" criteria. The results of this study indicate that the development of video-based learning media Adobe Flash CS6 is valid and effective to use.